2004
DOI: 10.1021/jp0401473
|View full text |Cite
|
Sign up to set email alerts
|

From Structure to Dynamics:  Modeling Exciton Dynamics in the Photosynthetic Antenna PS1

Abstract: Frequency domain spectra of the photosystem I (PS1) of Synechococcus elongatus are measured in a wide temperature range and explained in an exciton model based on the recently determined X-ray crystal structure. Using the known spatial positions and orientations of the chlorophylls (Chls) the dipole-dipole couplings between the chromophores are calculated. In contrast, the Chl Q y site energies are determined by a simultaneous fit of low-temperature absorption, linear dichroism, and circular dichroism spectra.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 38 publications
6
74
2
Order By: Relevance
“…(19), with ω c in the order of 100 cm −1 , has been used successfully to fit the optical dynamics in photosynthetic antenna complexes. 39,40,41,42 Also, Eq. (19) without a cutoff has been used to explain the optical dynamics of aggregates of the dye 3,3'-bis(sulfopropyl)-5,5'-dichloro-9-ethylthiacarbo-cyanine (THIATS) measured between 0 and 100 K. 43 In the remainder of this paper we will use ω c = 0.2J D , which is reasonable for J-aggregates, where J D typically lies in the range 500-1000 cm The above specifies all input necessary to determine the transfer rate W k ′ A,kD [Eq.…”
Section: Resultsmentioning
confidence: 99%
“…(19), with ω c in the order of 100 cm −1 , has been used successfully to fit the optical dynamics in photosynthetic antenna complexes. 39,40,41,42 Also, Eq. (19) without a cutoff has been used to explain the optical dynamics of aggregates of the dye 3,3'-bis(sulfopropyl)-5,5'-dichloro-9-ethylthiacarbo-cyanine (THIATS) measured between 0 and 100 K. 43 In the remainder of this paper we will use ω c = 0.2J D , which is reasonable for J-aggregates, where J D typically lies in the range 500-1000 cm The above specifies all input necessary to determine the transfer rate W k ′ A,kD [Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Multi-level Redfield theory was used to describe excitation energy transfer, e.g., between the strongly coupled BChls in the LH2 antenna complex (Kühn and Sundström 1997;Kühn et al 2002), in the reaction center of photosystem II (Leegwater et al 1997;Prokhorenko and Holzwarth 2000;Renger and Marcus 2002b), in the FMOprotein (Renger and May 1998;Adolphs and Renger 2006;Müh et al 2007), in photosystem I core complexes (Brüggemann et al 2004), in the LHC-II of green plants (Novoderezhkin et al 2003), in the core light-harvesting complex LH1 of purple bacteria (Novoderezhkin and van Grondelle 2002), in the WSCP complex , in the domains of strongly coupled Chls of photosystem II core complexes (Raszewski and Renger 2008), and in model dimers (Kjellberg and Pullerits 2006;Yang and Fleming 2002).…”
Section: Challenging Problems To Be Solved In the Futurementioning
confidence: 99%
“…In order to explain spectral and kinetic observations various modeling approaches based on the structural knowledge for Synechococcus elongatus has been performed recently (Sener et al 2002;Byrdin et al 2002;Damjanovic et al 2002;Yang et al 2003;Gobets et al 2003a, b;Bru¨ggemann et al 2004). By using full Coulomb couplings it is shown that the red spectral states can be attributed to four strongly coupled dimers (A32-B7 as C719; A33-A34 and A24-A35 as C715; B22-B34 as C708) (Sener et al 2002).…”
Section: Introductionmentioning
confidence: 99%